Reforma al art. 84 de la ley orgánica de defensa del consumidor en la que se incluye una audiencia oral de anunciación de prueba para garantizar el debido proceso - Briceño Cabrera, Jorge Fabián (2015)
Legal research entitled "REFORM ART. 84 OF THE ORGANIC LAW OF THE CONSUMER PROTECTION IN WHICH INCLUDES AN ORAL HEARING EVIDENCE ANNOUNCEMENT TO ENSURE THE DUE PROCESS" arises through through the study, which determined the need to guarantee the rights of the parties , as determined by the ongoing process because the Constitution of the Republic of Ecuador. As is logical and necessary to carry out the law firm in question currently, we have used various methods, with the help of which has been achieved Upon worked planned satisfactorily, for this reason is that in the first instance we have the scientific method, through which they could develop the procedure to be followed throughout the investigation, since it allowed this procedure to be logical and orderly, as the analysis and interpretation of scientific data collected require this type of treatment; the application of inductive - deductive method was feasible to obtain a general consideration, and particularly the issue in question; the analytical method - synthetic, was applied to the first of them, a stakeholder analysis entirely decomposed, and the second, the reunification of these units into a whole, the same as also was studied, thereby obtaining a comprehensive study of the problem; the comparative method, I used for the study of comparative law; the mayéutico method, assisted in part of the field research, since it was possible thanks to the development of the instruments; finally with the legal hermeneutic method, systematically interpreted the various standards relevant to this study. The data obtained by the application of the instruments were ordered, plotted and interpreted, in order to provide ease of understanding them, to the people who read this paper. The instruments used were the survey and interview, the first was built with thirty people, while the second with five. The study allowed further the need for a hearing of announcing test, in order to ensure due process within the Law on Consumer Protection. Consequently, a proposed legal reform to the rule mentioned above, that its essential purpose is, seeking the assurance of due process to the parties in a legal battle in which responsibilities are determined, in fulfillment of this arises way with the Constitution of the Republic of Ecuador